Evidence of persistent glial cell dysfunction in the anterior cingulate cortex of juvenile idiopathic arthritis children: a proton MRS study - Haiwei Han; Ji Hong Xiao; Yifei Weng; Hongyan Liang; Chengkun Han; Cuili Yi; Kezhao Lin; Hua Wu (BMC, 2022)
Abstract Background This study aims to investigate whether the neurometabolites of the anterior cingulate cortex (ACC) were distinct in patients with active and inactive juvenile idiopathic arthritis (JIA) using the proton magnetic resonance spectroscopy. Methods We measured the levels of total N-acetylaspartate (tNAA), choline (Cho), myo-inositol (ml), glutamate (Glu) and the complex of glutamate and glutamine (Glx) relative to total creatine (tCr) in ACC of each participant. Results Compared with the healthy controls, a significant decrease of total Cho/tCr and Glx/tCr ratio in ACC occurred in active and inactive JIA group. The tCho/Cr level was negatively associated with the serum level of ESR in active JIA patients. There was no difference in NAA/tCr ratio among the three groups, which may imply that no neuron and axonal losses occurred in either active or inactive JIA patients. Conclusions The abnormal neurometabolites in tCho/tCr and Glx/tCr in ACC may indicate that persistent dysfunction of glial cell, while neither neuron nor axonal losses occurred in active and inactive JIA patients.